Harnessing Microbial Allies: Sustainable Biological Control of Bacterial Blight in Pomegranate Cultivation - Shivam Satyawan Madrewar; Mahesh Sunil Pawar; Sangeeta Dhinwa; Anushka Anil Jadhav; Atharva Manish Gumphekar (MultiTech Publisher, 2024)
Bacterial blight, caused by Xanthomonas axonopodis pv. punicae, poses a severe threat to pomegranate (Punica granatum) cultivation, leading to significant economic losses and reduced fruit quality. Traditional chemical control methods have proven inadequate and environmentally harmful, highlighting the need for sustainable alternatives. This study investigates the potential of biological control as a viable solution for managing bacterial blight in pomegranates. We explore the efficacy of antagonistic microorganisms, including Bacillus spp., Pseudomonas spp., and Trichoderma spp., in suppressing the pathogen through mechanisms such as antibiosis, competition, and induced systemic resistance. Field trials demonstrate significant reductions in disease incidence and severity, alongside improved plant growth and yield. This research underscores the promise of integrating biocontrol agents into comprehensive disease management strategies, paving the way for a more sustainable and productive future in pomegranate agriculture.